2001
DOI: 10.1007/bf02850196
|View full text |Cite
|
Sign up to set email alerts
|

Oral beclomethasone dipropionate in patients with mild to moderate ulcerative colitis: A dose-finding study

Abstract: Systemic glucocorticosteroids have demonstrated efficacy in ulcerative colitis (UC) but cause undesired systemic side effects. Beclomethasone dipropionate (BDP) has potent topical activity and is extensively metabolized. This randomized double-blind study investigated an oral gastroresistant controlled-release preparation of BDP in 57 patients with mild to moderately severe extensive or left-sided UC. Patients were assigned to receive BDP 5 or 10 mg/d; a third group took a clinically inactive dose (1.6 g/d) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…11,31 Metabolites of BDP are systemically bioavailable, resulting in decreased adrenal responsiveness over time of drug exposure. 31,[44][45][46][47] Two recent studies of long-term use of oral, topically active corticosteroids in doses similar to those used in this trial demonstrated little evidence of clinical adrenal insufficiency. 45,48 Two randomized trials have shown that oral BDP prevents relapses of acute gastrointestinal GVHD after accelerated withdrawal of prednisone therapy.…”
Section: Discussionmentioning
confidence: 71%
“…11,31 Metabolites of BDP are systemically bioavailable, resulting in decreased adrenal responsiveness over time of drug exposure. 31,[44][45][46][47] Two recent studies of long-term use of oral, topically active corticosteroids in doses similar to those used in this trial demonstrated little evidence of clinical adrenal insufficiency. 45,48 Two randomized trials have shown that oral BDP prevents relapses of acute gastrointestinal GVHD after accelerated withdrawal of prednisone therapy.…”
Section: Discussionmentioning
confidence: 71%
“…In previous studies, the role of rectal formulation of BDP in treatment of UC has been evaluated in comparison with 5-ASA or prednisolone sodium phosphate enemas showing similar efficacy for mild or moderate distal disease. [8][9][10][11][12][13][14][15][16][17][18] A standard dose of BDP 5 mg od (1 tablet day) has been established in the study conducted by Rizzello et al 9 In this study, administration of 5 mg or 10 mg daily showed therapeutic equivalence in patients affected by mild to moderate extensive or left-sided UC, whilst morning plasma cortisol level decreased in the 10 mg group without changes in vital signs. Oral BDP at a standard dose has been studied in treatment of active extensive or left-sided UC, either in combination with 5-ASA or alone resulting effective and safe, without signs of pituitaryadrenal function impairment.…”
Section: Discussionmentioning
confidence: 93%
“…8 For active mild or moderate extensive or left-sided UC, BDP oral preparation (5 mg tablets) is administered at the recommended dosage of 1 tablet od either in combination with 5-ASA or alone. 9 Since the tablet dissolves at pH values of less than 6.0, the oral delayed-release preparation of BDP is effective in the distal small bowel and throughout the colon. 10,11 Despite its promising characteristics and encouraging results, role of BDP in clinical practice still needs to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Oral BDP is effective in improving clinical, endoscopic and biopsy scores in patients with mild-to-moderate left-sided and extensive UC [58,59,60,61,62]. The efficacy of BDP is higher when associated with mesalazine products [59], and was equivalent to oral prednisone in the BETA study [unpubl.…”
Section: Resultsmentioning
confidence: 99%